Identification of three amino acid residues in the B subunit of Shiga toxin and Shiga-like toxin type II that are essential for holotoxin activity. - Perera, L P (1991)
Shiga toxin of Shigella dysenteriae type I and Shiga-like toxins I and II (SLT-I and SLT-II, respectively) of enterohemorrhagic Escherichia coli are functionally similar protein cytotoxins. These toxin molecules have a bipartite molecular structure which consists of an enzymatically active A subunit that inhibits protein synthesis in eukaryotic cells and an oligomeric B subunit that binds to globotriaosylceramide glycolipid receptors on eukaryotic cells. Regionally directed chemical mutagenesis of the B subunit of SLT-II was used to identify amino acids in the B subunit that are critical for SLT-II holotoxin cytotoxic activity. Three noncytotoxic mutants were isolated, and their mutations were mapped. The substitutions of arginine with cysteine at codon 32, alanine with threonine at codon 42, and glycine with aspartic acid at codon 59 in the 70-amino-acid mature SLT-II B polypeptide resulted in the complete abolition of cytotoxicity. The analogous arginine, alanine, and glycine residues were conserved at codons 33, 43, and 60 in the 69-amino-acid mature B polypeptide of Shiga toxin. Comparable mutations induced in the B-subunit gene of Shiga toxin by oligonucleotide-directed, site-specific mutagenesis resulted in drastically decreased cytotoxicity (10(3)- to 10(6)-fold) as compared with that of wild-type Shiga toxin. The mutant SLT-II and Shiga toxin B subunits were characterized for stability, receptor binding, immunoreactivity, and ability to be assembled into holotoxin.